1993
DOI: 10.1083/jcb.122.6.1223
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional transcytosis determines the steady state distribution of the transferrin receptor at opposite plasma membrane domains of BeWo cells

Abstract: Abstract. Trophoblast-like BeWo cells form wellpolarized epithelial monolayers, when cultured on permeable supports. Contrary to other polarized cell systems, in which the transferrin receptor is found predominantly on the basolateral cell surface, BeWo cells express the transferrin receptor at both apical and basolateral cell surfaces (Cerneus, D.P., and A. van der Ende. 1991. J. Cell Biol. 114: 1149-1158. In the present study we have addressed the question whether BeWo cells use a different sorting mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
1
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 25 publications
3
33
1
1
Order By: Relevance
“…Cells from a confluent culture in an 80 cm# culture flask were obtained by trypsinization and were suspended in 20 ml culture medium of which 1 ml was added per filter. The tightness of the monolayer was checked routinely by adding medium to the upper chamber up to a higher level than in the lower chamber (Cerneus et al, 1993 ;Rossen et al, 1994).…”
Section: Methodsmentioning
confidence: 99%
“…Cells from a confluent culture in an 80 cm# culture flask were obtained by trypsinization and were suspended in 20 ml culture medium of which 1 ml was added per filter. The tightness of the monolayer was checked routinely by adding medium to the upper chamber up to a higher level than in the lower chamber (Cerneus et al, 1993 ;Rossen et al, 1994).…”
Section: Methodsmentioning
confidence: 99%
“…For the transferrin receptor, it has been shown that 80% of newly synthesized receptor is initially inserted into the basolateral domain. The steady-state distribution is then achieved by different rates of transcytosis of apical and basolateral receptors (Cerneus et al 1993a). It remains to be demonstrated whether newly synthesized PLAP is initially sorted to the apical domain and subsequently transcytosed to the basolateral side, with less transcytosis taking place in the opposite direction in BeWo cells.…”
Section: Figurementioning
confidence: 99%
“…in a two-chamber system for 5 days. Under these conditions, BeWo cells form a tight, polarized monolayer that mimicked the trophoblastic barrier in vivo (12,13). We checked the integrity of target BeWo cell monolayers at the onset of the experiments and after contact with infectious material by using three parameters.…”
Section: Cellsmentioning
confidence: 99%